An iterative boundary element method for a wing-in-ground effect - Kinaci, Omer Kemal (SOC NAVAL ARCHITECTS KOREA, 2014)
In this paper, an iterative boundary element method (IBEM) was proposed to solve for a wing-in-ground (WIG) effect. IBEM is a fast and accurate method used in many different fields of engineering and in this work; it is applied to a fluid flow problem assessing a wing in ground proximity. The theory and the developed code are validated first with other methods and the obtained results with the proposed method are found to be encouraging. Then, time consumptions of the direct and iterative methods were contrasted to evaluate the efficiency of IBEM It is found out that IBEM dominates direct BEM in terms of time consumption in all trials. The iterative method seems very useful for quick assessment of a wing in ground proximity condition. After all, a NACA6409 wing section in ground vicinity is solved with IBEM to evaluate the WIG effect.
Keywords: Iterative boundary element method; Wing-in-ground effect; Method of images; NACA6409; AERODYNAMIC CHARACTERISTICS; WAVE PATTERN; PREDICTION; Engineering